2017
DOI: 10.1038/s41598-017-13920-0
|View full text |Cite
|
Sign up to set email alerts
|

Marine self-potential survey for exploring seafloor hydrothermal ore deposits

Abstract: We conducted a self-potential survey at an active hydrothermal field, the Izena hole in the mid-Okinawa Trough, southern Japan. This field is known to contain Kuroko-type massive sulphide deposits. This survey measured the self-potential continuously in ambient seawater using a deep-tow array, which comprises an electrode array with a 30-m-long elastic rod and a stand-alone data acquisition unit. We observed negative self-potential signals not only above active hydrothermal vents and visible sulphide mounds bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 41 publications
5
42
0
1
Order By: Relevance
“…A similar phenomenon was also reported from a self-potential survey in a deep-sea hydrothermal field. [8] Negative self-potential signals were observed above active hydrothermal vents, visible sulfide mounds and Figure 2. Fuel-cell-type electricity generation at an artificial deep-sea hydrothermal vent.…”
Section: Widespread Electric Discharge In Deep-sea Hydrothermal Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar phenomenon was also reported from a self-potential survey in a deep-sea hydrothermal field. [8] Negative self-potential signals were observed above active hydrothermal vents, visible sulfide mounds and Figure 2. Fuel-cell-type electricity generation at an artificial deep-sea hydrothermal vent.…”
Section: Widespread Electric Discharge In Deep-sea Hydrothermal Fieldsmentioning
confidence: 99%
“…These results indicate widespread and distant electron transfer occurs from the subseafloor hydrothermal fluid to the ambient seawater via electrically conductive, massive hydrothermal mineral deposits (Figure ). A similar phenomenon was also reported from a self‐potential survey in a deep‐sea hydrothermal field . Negative self‐potential signals were observed above active hydrothermal vents, visible sulfide mounds and the seafloor without such structures.…”
Section: Electricity Generation In Deep‐sea Hydrothermal Fieldsmentioning
confidence: 99%
“…SP is an attractive technique for detecting marine ore deposits associated with geothermal activity (Kawada and Kasaya ). The reasons for this are the reduced noise levels and the ability to contact continuous measurements (Kawada and Kasaya ).…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…), geothermal exploration (Corwin and Hoover ), volcanology (Fournier ; Aizawa ), coal fire detection (Shao et al . , ), hydrothermal ore deposits (Kawada and Kasaya ) and marine mineral deposits (Heinson et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Geophysical mapping methods, which continuously observe signals away from the seafloor, might be the best choice for this purpose. Using a deep-towed array, we have demonstrated that the self-potential method, which measures in situ electrostatic potential (e.g., Jouniaux and Ishido 2012;Revil and Jardani 2013), works effectively to locate seafloor hydrothermal ore deposits (Kawada and Kasaya 2017). The observed self-potential signals are likely to detect redox reactions occurring around an ore body as a negative self-potential anomaly above it (Sato and Mooney 1960).…”
Section: Introductionmentioning
confidence: 99%